2015
DOI: 10.17223/19988591/31/5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-genetic characteristic of Pelophylax esculentus complex from the eastern range of distribution (Volga region, Tatarstan Republic)

Abstract: Molecular-genetic characteristic of Pelophylax esculentus complex from the eastern range of distribution (Volga region, Tatarstan Republic) We studied patterns of the Pelophylax esculentus complex population-genetic system at the eastern border of their distribution range (Volga region, Tatarstan Republic) and such cryptic forms as Pelophylax ridibundus (Pallas, 1771) and P. cf. bedriagae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…During the five years of our study on frogs, 135 individuals of water frogs from 15 localities in various regions of Central Russia were analysed by the use of multiplex PCR (Svinin et al, 2015;Zamaletdinov et al, 2015;Ivanov et al, 2016;Fayzulin et al, 2018). A natural introgression of mtDNA in any non-clonal species of water frogs has never been observed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the five years of our study on frogs, 135 individuals of water frogs from 15 localities in various regions of Central Russia were analysed by the use of multiplex PCR (Svinin et al, 2015;Zamaletdinov et al, 2015;Ivanov et al, 2016;Fayzulin et al, 2018). A natural introgression of mtDNA in any non-clonal species of water frogs has never been observed.…”
Section: Resultsmentioning
confidence: 99%
“…bedriagae (B-RR). Such combination of mt and nDNA markers is common for marsh frogs from the Middle Volga River basin (Ermakov et al, 2014;Zamaletdinov et al, 2015;Fayzulin et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, to approach the above questions, we investigated the water frogs from western Russian territory, of which populations are located 800 km west from the eastern end of their geographic distribution ( Figure 1 ). To date, few genetic studies have included the populations [ 18 ] and the unusual situation of hybridogenesis in the water frog complex is expected to be brought about by immigration of levant frog P. bedriagae into the Russian territories [ 19 , 20 , 21 ]. Our study identified a variation in the genome elimination within one population.…”
Section: Introductionmentioning
confidence: 99%